Primary stroke prevention and hypertension treatment: which is the first-line strategy? - Roberta Ravenni; Joe Jabre; Edoardo Casiglia; Alberto Mazza (MDPI AG, 2011)
Hypertension (HT) iis considered the main classic vascular risk factor for stroke and the importance of lowering blood pressure (BP) is well established. However, not all the benefit of antihypertensive treatment is due to BP reduction per se, as the effect of reducing the risk of stroke differs among classes of antihypertensive agents. Extensive evidences support that angiotensin-converting enzyme inhibitors (ACEI), angiotensin II receptor blockers (ARB), dihydropyridine calcium channel blockers (CCB) and thiazide diuretics each reduced risk of stroke compared with placebo or no treatment. Therefore, when combination therapy is required, a combination of these antihypertensive classes represents a logical approach. Despite the efficacy of antihypertensive therapy a large proportion of the population, still has undiagnosed or inadequately treated HT, and remain at high risk of stroke. In primary stroke prevention current guidelines recommend a systolic/diastolic BP goal of <140/<90 mmHg in the general population and <130/80 mmHg in diabetics and in subjects with high cardiovascular risk and renal disease. The recent release in the market of the fixed-dose combination (FDC) of ACEI or ARB and CCB should provide a better control of BP. However to confirm the efficacy of the FDC in primary stroke prevention, clinical intervention trials are needed.